Pre-column dervatization of amino acids from nigella sativa L seed hydrolysates by reversed phase HPLC (Baghdad Science Journal, 2008)
A rapid and sensitive method for analysis of amino acid hydrolysates of nigella sativa L seed has been developed using O-phthaldialehyde(OPA ) as a pre-column derivatizing agent. OPA reagents in the presence of mercaptoethanol react rapidly with primary amino acids ( less than 60 sec.) to form isindole derivatives which easily separated with good selectivity on ODS column. Resolution of amino acid derivatives is carried out with a methanol gradient in 0.01 maqueous sodium acetate. pH 7.1 . The quantitation of amino acid derivatives is reproducible within an average relative deviation of + 1.4% the linearity for most amino acids were more than 0.9993 with detection limit of 0.2 ppm. 15 amino acid were detected in the analysis of the seed protein hydrolysate. The presence of glutamic acid, alanine, leucine, cystine phenylalanine, aspartic acid in large quantities. The common separated amino acids were detected by U.V at 338 nm within 21 minutes.